Defensive Use of Prior Art to Exonerate Accused Acts in U.S. and Chinese Patent Litigation - Lau, Timothy (Columbia Journal of Asian Law, 2013)
It is a fundamental principle of patent law that no one may exclude with his patent what is within the scope of the prior art. This article focuses on the ‘practicing the prior art’ defense, where the defendant defensively demonstrates that the accused acts fall within the prior art and therefore may be freely practiced, as implemented in U.S. and Chinese jurisprudence. A defendant in U.S. patent litigation has no recourse to this defense with respect to literal infringement, and his options with regard to prior art defenses is limited to the offensive variant, prior art invalidity. In contrast, a defendant in a Chinese infringement suit may only invoke this defensive variant of the prior art defenses. We explore the rationale for and against the existence of the practicing the prior art defense, and examine the peculiarities of the Chinese approach of tying its practicing the prior art defense to the doctrine of equivalents.